Psychotherapy in Africa: experience of the group psycho-educational support programme at Ibadan - a preliminary report (1995)
Africa stem from the lack of an appropriate psychodynamic theory ori which to base the technique used. He suggested and experimented with the use of cosmologies (world view) native to the culture (e.g. - the Yoruba Ayanmo myth) in psychodynamic elaborations in therapy. Ohaeri (1989) believed that work along the lines suggested by Morakinyo (1982) be encouraged, but opined that the current socio-economic and cultural changes in Nigeria make it imperative to examine the need for formalized psychotherapy in the contemporary Nigeria. In view of the above coupled with the felt needs of the teaming number of oncology patients at the Cancer Registry of the University College Hospital (U.C.H.), Ibadan, the Lola Marinho Psycho-oncology Counselling Clinic (LMPOC2) was established in July 1992. The clinic now runs a formal psychotherapy programme. With the increased availability of modern methods for diagnosis and the treatment of cancer, our experience has shown that many more cases of cancer now report in hospitals in Nigeria, in particular, at the Radio-therapy Centre of the University College Hospital (U.C.H.), Ibadan, which is the only functioning radio-therapy centre in West Africa sub-region for now. This has offered us the opportunity to enquire into aspects of psycho-oncology. Our goals in this clinic are: 1. to assist the patients and heir family members in becoming more knowledgeable about the disease by providing them with all necessary information. 2. to give support by providing continuity of care. 3. to teach the patients and their family members the necessary skills to cope with the stress of living with cancer. It is an eight session progressive course, which we have developed and used for hundreds of patients at the Lola Marinho Psycho-oncology Counselling Clinic (LMPOC2). The programme is intended for people living with cancer who want to help themselves cope with and combat their disease. It is also meant for those who wish to conduct group teaching skills for people living with cancer and their family members. The paper deals with the efficacy of psychotherapy in improving the quality of life of oncology patients in Nigeria, judging from our experience with our clients at the Lola Marinho Psycho-oncology Counselling Clinic (LMPOC2) of the University College Hospital, Ibadan, Nigeria. The findings pose great challenges to all categories of health care providers, especially Nigerian psychologists